Integrated fundal assessment pathway for patients with suspected shunt malfunction via digital retinal images. (1st November 2020) - Akhunbay-Fudge, C.; Evans, F.; Long, V.; Chumas, P.; Corns, R.; Sheikh, A.
Abstract: Introduction: Papilloedema is an important clinical sign in the assessment of neurosurgical patients presenting with suspected shunt malfunction. Methods: We describe our 18-month experience using a newly acquired nonmydriatic digital retinal camera to acquire fundal photographs for this purpose. Results: It was used to take digital photographs in 67 patients presenting with suspected shunt malfunction and 54% of these images were discussed with the on-call ophthalmology team for advice. Of these 81% had instant input provided by ophthalmology and the remainder were sent to the ophthalmology department for formal assessment. Of all shunt related regional referrals in the same time period, we found that only 13% of the referred patients were discussed with the on-call ophthalmology team. The rest had decisions made by the on-call neurosurgical team. Conclusions: We believe this new integrated pathway is clinically and cost-effective and recommend it as a useful tool in other neurosurgical units.